2011
DOI: 10.1038/ki.2011.282
|View full text |Cite
|
Sign up to set email alerts
|

Selective albuminuria via podocyte albumin transport in puromycin nephrotic rats is attenuated by an inhibitor of NADPH oxidase

Abstract: The mechanism of selective albuminuria in minimal change nephrotic syndrome, in which glomerular capillaries are diffusely covered by effaced podocyte foot processes with reduced slit diaphragms, is unknown. Podocyte injury is due, in part, to NADPH-induced oxidative stress. Here we studied mechanism of selective albuminuria in puromycin aminonucleoside (PAN) nephrotic rats, a model of minimal change nephrotic syndrome. In these rats, Evans Blue-labeled human albumin was taken up by podocytes and its urinary e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
76
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 68 publications
(81 citation statements)
references
References 53 publications
4
76
1
Order By: Relevance
“…42 In accordance with a clearance function of podocytes, the blockade of the fetal Fc fragment receptor, which is relevant for intracellular albumin vesicle sorting, caused a reduction in proteinuria in nephrotic rats. 25 Furthermore, fetal Fc fragment receptor-deficient mice accumulated IgG in the glomerular basement membrane, further supporting the assumption that podocytes have a clearance function for the glomerular filtration barrier. 16,17 We found that endocytosed albumin is partly localized in acid cell compartments, which colocalized with the lysosomal marker LysoTracker in vivo.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…42 In accordance with a clearance function of podocytes, the blockade of the fetal Fc fragment receptor, which is relevant for intracellular albumin vesicle sorting, caused a reduction in proteinuria in nephrotic rats. 25 Furthermore, fetal Fc fragment receptor-deficient mice accumulated IgG in the glomerular basement membrane, further supporting the assumption that podocytes have a clearance function for the glomerular filtration barrier. 16,17 We found that endocytosed albumin is partly localized in acid cell compartments, which colocalized with the lysosomal marker LysoTracker in vivo.…”
Section: Discussionmentioning
confidence: 59%
“…24 Data obtained from human, rat, and mouse kidneys suggested that plasma proteins, such as IgG, ferritin, and albumin, may be localized in podocyte vacuoles. 8,17,[25][26][27][28][29][30] Commensurate with these findings, podocytes were suggested to clear the glomerular filtration barrier from proteins. 17 Our results are in agreement with these studies and further reveal that an Ang II-mediated increase in albumin flux across the glomerular membrane enhances the endocytosis of albumin by podocytes in the normal glomerulus.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Numerous studies using electron microscopy have shown increased numbers of protein-containing vesicles in podocytes under nephrotic conditions in which there is significant leakage of proteins across the GBM (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18). Previously, we showed that expression of the neonatal Fc receptor, a transcytosis receptor for Ig and albumin, allows podocytes to handle these proteins by internalization and transcytosis (19).…”
Section: Introductionmentioning
confidence: 99%
“…In animal models of minimal change disease, membranous nephropathy, and FSGS, inhibition of Nox activity is associated with decreased podocyte effacement and amelioration of albuminuria. [11][12][13][14] In models of diabetic nephropathy, treatment with the Nox inhibitor apocynin, as well the antioxidant vitamin E, reduces oxidative stress, podocyte effacement and loss, and albuminuria. 6,15,16 Noxs are regulated by many factors, including the renin angiotensin aldosterone system.…”
mentioning
confidence: 99%